Психоаналитические концепции эмоционального выгорания - Irina V. Laikova (Российский психологический журнал, 2016)
The article describes the psychoanalytic concepts of study of the burnout phenomenon, which are based on qualitative approach. This approach is complementary to studies concentrated in the Yeld of organizational and social psychology which are mostly quantitative by nature and give limited insight into the dynamics of burnout and personal meanings, associated with it. Psychoanalytic studies mainly address two aspects of burnout, namely a disruption of professional identity of people and diZculties at the intersubjective level which are closely interlinked. The tripartite conceptual model of S. Vanheule and P. Verhaeghe is shown which is based on the schema of J. Lacan’s “two mirrors” re[ecting three dynamic rocesses accompanying subjective experience of “burned out” professionals. Alternative models and explanatory concepts of burnout concordant with presented dynamic processes are considered. According to J. Lacan, the processes re[ect the functioning of the mental instances of the Ego, ideal Ego, Ego-ideal and Superego in the process of an increment of subjective knowledge. In the light of the psychoanalytic concepts, emotional burnout is treated as a crisis of identity, generated from the problems of formation of subjectivity in intersubjective interactions. This, in turn, allows to attribute emotional burnout as a general psychological phenomenon, not solely related to the professional activities. The basis of emotional burnout lies in the unconscious con[ict between conscious needs and unconscious drives resulting in the blocking activity and the alienation of the subject from certain aspects of his being. IdentiYcation and analysis of unconscious contradictions, leading to a tension and stagnation of the subject, seems to be promising for prevention and overcoming of the burnout.